COMPONENTS AND INDICATORS OF EDUCATION MANAGEMENT ACCORDING TO SUB-DISTRICT NON-FORMAL AND INFORMAL EDUCATION CENTRE STANDARDS FOR EXCELLENCE - Arsathong, Sanit; Julsuwan, Suwat (International Online Journal of Education and Teaching, 2024)
The research aims to study components and indicators of education management according to Sub – District Non – Formal and Informal Education Centre Standards for Excellence. The researcher studies principles, concepts, and theories from documents, textbooks, and related research both domestically and internationally. Then gather information analyze and synthesize data. To obtain the components and indicators of educational management according to the Sub – District Non – Formal and In-Formal Education Centre Standards for Excellence. The tools used for data collection were document recording forms and a form to assess the suitability of components and indicators by confirming the elements and indicators from the 9 experts. The results of the study showed that 1) the Components and Indicators of Education Management according to Sub-District Non-Formal and Informal Education Centre Standards for Excellence consisted 7 components: (1) Organizational Leadership, (2) Strategic Planning, (3) Learner and Stakeholder focus, (4) Measurement, Analysis, and Knowledge Management, (5) Personnel focus, (6) Process management, and (7) outcomes. 2) Organizational leadership elements and indicators. It is most appropriate. 3) Strategic planning elements and indicators. It is the most appropriate. 4) Elements and indicators of learner and stakeholder focus are most appropriate. 5) Elements and indicators of measurement, analysis, and knowledge management are very appropriate. 6) Composition and indicators of personnel focus. It is very appropriate. 7) Process management elements and indicators. It is the most appropriate.